Self-acceptance of Mothers who have Children with Special Needs - Eriza Dwi Putri Islami; Eko Hardi Ansyah (Indonesian Journal of Cultural and Community Development, 2020)
This study aims to describe students who have children with special needs and describe what factors affect mothers who have expectional children. The method used in this study is qualitative with case study desig. Research subjects were mothers of expectional children with the type of mental retardation, hearing impairment and cerebral palsy. Determination of research subjects using purposive sampling. Data collection method used are interview and observation techniques. The results of this study indicated that the description of acceptance of self from the three mothers has expectional children, namely accepting the conditions experienced, still ditions experienced. Factors that influense the formation of self acceptanse are education, social support, family and religious parenting.